Numerical methods for microstructural evolutions in laser additive manufacturing. (1st October 2019) - Zhang, Z.; Tan, Z.J.; Yao, X.X.; Hu, C.P.; Ge, P.; Wan, Z.Y.; Li, J.Y.; Wu, Q.
Abstract: Different methods are developed for simulation of microstructural evolution in metals and alloys subject to Laser Additive Manufacturing. The Monte Carlo (MC) method is combined with a new proposed two scales strategy for simulation of the solidification and the subsequent solid-state phase transformation in Ti–6Al–4V.The Cellular Automaton (CA) method shows its higher efficiency in comparison with MC method. Moore neighbor type with energy barrier is recommended for the CA simulation of grain growth of Al 6061. The phase field (PF) model shows that different temperature gradients lead to different columnar grains in different layers of Ti–32wt.%Nb. The computed structures are related to experimental observations.